2003
DOI: 10.1074/jbc.m208872200
|View full text |Cite
|
Sign up to set email alerts
|

RICS, a Novel GTPase-activating Protein for Cdc42 and Rac1, Is Involved in the β-Catenin-N-cadherin andN-Methyl-d-aspartate Receptor Signaling

Abstract: Cadherin adhesion molecules are believed to be important for synaptic plasticity. ␤-Catenin, which links cadherins and the actin cytoskeleton, is a modulator of cadherin adhesion and regulates synaptic structure and function. Here we show that ␤-catenin interacts with a novel GTPase-activating protein, named RICS, that acts on Cdc42 and Rac1. The RICS-␤-catenin complex was found to be associated with N-cadherin, N-methyl-D-aspartate receptors, and postsynaptic density-95, and localized to the postsynaptic dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
116
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 81 publications
3
116
0
Order By: Relevance
“…In vivo pull-down assays suggest that p250GAP potentially regulates several Rho family GTPases (16)(17)(18)(19)(20), and cerebellar granule cells from p250GAP-knockout mice show increased Cdc42 activity (18). p250GAP is enriched in the postsynaptic density where it interacts with the NMDA NR2B receptor subunit and the scaffold protein PSD-95 (25,26). p250GAP also interacts with Fyn (17), a tyrosine kinase that phosphorylates NR2B and regulates NMDA-dependent neuronal plasticity (27).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo pull-down assays suggest that p250GAP potentially regulates several Rho family GTPases (16)(17)(18)(19)(20), and cerebellar granule cells from p250GAP-knockout mice show increased Cdc42 activity (18). p250GAP is enriched in the postsynaptic density where it interacts with the NMDA NR2B receptor subunit and the scaffold protein PSD-95 (25,26). p250GAP also interacts with Fyn (17), a tyrosine kinase that phosphorylates NR2B and regulates NMDA-dependent neuronal plasticity (27).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate receptor and Rho GTPase have been proposed to be essential to dendrite growth in Xenopus (Sin et al, 2002). A Rho-GAP, RICS (Okabe et al, 2003) as well as several Rac/Cdc42-specific Rho-GEF, such as Kalirin-7 (Penzes et al, 2001), dPix (Parnas et al, 2002) and bPIX (Park et al, 2003), have been reported to play a role in dendrite remodeling. These reports are focusing on the involvement of Rho GTPases in dendritic morphogenesis through NMDA receptor and suggest that Rac and AMPA, not NMDA, activates RhoA GTPases and subsequetly phosphorylates m oesin Cdc42 activities enhance dendritic remodeling while RhoA activity inhibits (Wong et al, 2000;Li et al, 2002;Sin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…RICS is expressed predominantly in neurons of the brain and localized to the growth cone and postsynaptic density, where it regulates neurite extension and presumably N-methyl-D-aspartate signaling (14). In contrast, PX-RICS is expressed in a wide variety of tissues and cell lines and localized to the ER and cis-Golgi (13,15).…”
mentioning
confidence: 99%
“…Classic cadherins (simply referred to cadherins hereafter) (5-9), however, are known to have no functional ER export motifs, and their efficient ER exit requires complex formation with ␤-catenin at the ER immediately after cadherin synthesis (10 -12). We have recently shown that this ␤-catenin-facilitated ER export of cadherins requires PX-RICS, a ␤-catenininteracting GTPase-activating protein (GAP) for Cdc42 (13).PX-RICS is an alternatively spliced isoform of RICS (RhoGAP involved in the ␤-catenin-N-cadherin and N-methyl-D-aspartate receptor signaling) and contains phox homology (PX) and Src homology 3 domains in its N-terminal region (14,15). RICS is expressed predominantly in neurons of the brain and localized to the growth cone and postsynaptic density, where it regulates neurite extension and presumably N-methyl-D-aspartate signaling (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation